Observation of magnetic skyrmion lattice in Cr0.82Mn0.18Ge by small-angle neutron scattering - Victor Ukleev; Tapas Samanta; Oleg I. Utesov; Jonathan S. White; Luana Caron (Scientific Reports)
Abstract Incommensurate magnetic phases in chiral cubic crystals are an established source of topological spin textures such as skyrmion and hedgehog lattices, with potential applications in spintronics and information storage. We report a comprehensive small-angle neutron scattering (SANS) study on the B20-type chiral magnet Cr $$_{0.82}$$ Mn $$_{0.18}$$ Ge, exploring its magnetic phase diagram and confirming the stabilization of a skyrmion lattice under low magnetic fields. Our results reveal a helical ground state with a decreasing pitch from 40 to 35 nm upon cooling, and a skyrmion phase stable in applied magnetic fields of 10–30 mT, and over an unusually wide temperature range for chiral magnets of 6 K ( $$\sim T_\text {C}/2< T < T_\text {C}$$ , $$T_\text {C}=13$$ K). The skyrmion lattice forms a standard two-dimensional hexagonal coordination that can be trained into a single domain, distinguishing it from the three-dimensional hedgehog lattice observed in MnGe-based systems. Additionally, we demonstrate the persistence of a metastable SkL at 2 K, even at zero field. These findings advance our understanding of magnetic textures in Cr-based B20 compounds, highlighting Cr0.82Mn0.18Ge as a promising material for further exploration in topological magnetism.